Psychological Treatment of Depression in People Aged 65 Years and Over: A Systematic Review of Efficacy, Safety, and Cost-Effectiveness. - Ulf Jonsson; Göran Bertilsson; Per Allard; Harald Gyllensvärd; Anne Söderlund; Anne Tham; Gerhard Andersson (PLoS ONE, 2016)
Objectives Depression in elderly people is a major public health concern. As response to antidepressants is often unsatisfactory in this age group, there is a need for evidence-based non-pharmacological treatment options. Our objectives were twofold: firstly, to synthesize published trials evaluating efficacy, safety and cost-effectiveness of psychological treatment of depression in the elderly and secondly, to assess the quality of evidence. Method The electronic databases PubMed, EMBASE, Cochrane Library, CINAL, Scopus, and PsycINFO were searched up to 23 May 2016 for randomized controlled trials (RCTs) of psychological treatment for depressive disorders or depressive symptoms in people aged 65 years and over. Two reviewers independently assessed relevant studies for risk of bias. Where appropriate, the results were synthesized in meta-analyses. The quality of the evidence was graded according to GRADE (Grading of Recommendations Assessment, Development and Evaluation). Results Twenty-two relevant RCTs were identified, eight of which were excluded from the synthesis due to a high risk of bias. Of the remaining trials, six evaluated problem-solving therapy (PST), five evaluated other forms of cognitive behavioural therapy (CBT), and three evaluated life review/reminiscence therapy. In frail elderly with depressive symptoms, the evidence supported the efficacy of PST, with large but heterogeneous effect sizes compared with treatment as usual. The results for life-review/reminiscence therapy and CBT were also promising, but because of the limited number of trials the quality of evidence was rated as very low. Safety data were not reported in any included trial. The only identified cost-effectiveness study estimated an incremental cost per additional point reduction in Beck Depression Inventory II score for CBT compared with talking control and treatment as usual. Conclusion Psychological treatment is a feasible option for frail elderly with depressive symptoms. However, important questions about efficacy, generalizability, safety and cost-effectiveness remain.